Drag on sports balls using Doppler radar - Martin, J.; Smith, L. V.; Kensrud, J. R. (Procedia Engineering, 2012)
Aerodynamic drag on sports balls is typically measured in laboratory wind tunnels or by projecting balls through still air. With the advent of Doppler radar and sophisticated tracking software, pitched and hit balls can be tracked throughout the trajectory in game conditions. The following considers drag measurements from balls hit in a game setting using a Doppler tracking system. The effects of spin, seam height, and velocity on drag were explored. The trends were compared to laboratory drag measurements from balls projected through still air. Balls with raised seams had, on average, higher drag than flat seam balls. Over speeds representative of play conditions, the ball drag coefficient decreased with increasing ball speed. It was also found that an increase in spin rate did not correlate to an increase in the drag coefficient.